MEDICINAL PROPERTIES OF PLANTAGO MAJOR L. - Turakulov Alimardon Abdusalomovich, Egamberdiyev Murodjon Xolmirzayevich, Abdunazarov Sherzod Xushbo (International Journal of Literature and Language Studies, 2026)
This article provides information about the Zubturum plant, its importance, and medicinal properties. Zubturum is a perennial plant and is a representative of the Zubturum family. Currently, it includes about 260 species. Of these, 6 species are found in Uzbekistan. Zubturum is also of particular importance in folk medicine. This is because this plant has been used in medicine since ancient times, and it cures more than 80 diseases. Studying the composition of the Zubturum plant shows that it can be used even more in the currently developing field of pharmacology.